Tendencies towards Consumptive Behavior in Members of Student Activity Groups at University X - Gabriela Wilona Karen; Arfian (Insight School Academy, 2024)
Introduction to The Problem : This research aims to examine the relationship between self-concept and the tendency towards consumerist behavior among student members of extracurricular activity units (UKMs) at University X. Purpose : This research aims to investigate the correlation between self-concept and the tendency for consumerist behavior among student members of extracurricular activity groups (UKM) at University X. Design/methods/approach: This research employs a quantitative approach with a correlational design. The subjects of this study are members of student activity units (UKMs) at University X, with a sample size of 108 students. Findings : Hasil penelitian menunjukkan skor koefisien korelasi sebesar 0,385 dengan nilai signifikansi 0,000. Research implications/limitations: This research indicates a significant positive correlation between self-concept and consumer behavior among members of student activity groups (UKMs) at University X. This means that a higher self-concept is associated with higher consumer behavior, and conversely, a lower self-concept is associated with lower consumer behavior.